PEMBELAJARAN EXPERIMENT MELALUI MODEL PROBLEM SOLVING TERHADAP PENGUASAAN BAHASA INGGRIS (STUDI ANALISIS DI LEMBAGA GALAXY INSTITUTE PARE KEDIRI) - Roslan Muhammad; Alita Hasan (Cakrawala Bahasa, 2022)
The study of descriptive non formal institutions such as English course institutions in the English village of pare Kediri is very to explore. Especially the English village of pare has became an icon of English education tourism. The purpose of this study is to analyze the application of experimental learning through problem solving models to mastery of English at the galaxy institute. The research method used is qualitative research with a case study approach. The result of the study indicate that the application of experimental learning and problem solving is used in the learning process at galaxy institute, which is conveyed in the curriculum and SOP of the institution. So that all units are involved to carry out both institute directors, tutor as well as students. In practice the application of experimental learning must be in accordance with the problem faced by the students and problem solving learning at the galaxy institute means that tutor or educators are present as problem solving so that learning materials and methods are adapted to the needs of students.